Differences in the Late Positive Potential and P300 to Emotional Faces in Individuals with Autism Spectrum Disorder. - Keifer, Cara M.; Hauschild, Kathryn M.; Nelson, Brady D.; Hajcak, Greg; Lerner, Matthew D. (Journal of Autism & Developmental Disorders, 2019)
Despite evidence suggesting differences in early event-related potential (ERP) responses to social emotional stimuli, little is known about later stage ERP contributions to social emotional processing in individuals with autism spectrum disorder (ASD). Adults with and without ASD completed a facial emotion recognition task involving stimuli that varied by emotional intensity while electroencephalograms were recorded. Principal components analysis was used to examine P300 and late positive potential (LPP) modulation by emotional intensity. Results indicated that greater ASD symptomatology evinced heightened P300 to high relative to low intensity faces, then heightened LPP to low relative to high intensity faces. Findings suggest that adults with greater ASD symptomatology may demonstrate a lag in engagement in elaborative processing of low intensity faces.